Ambient annealing influence on surface passivation and stoichiometric analysis of molybdenum oxide layer for carrier selective contact solar cells. (1st March 2019) - Hussain, Shahzada Qamar; Mallem, Kumar; Kim, Yong Jun; Tuan Le, Anh Huy; Khokhar, Muhammad Quddamah; Kim, Sehyeon; Dutta, Subhajit; Sanyal, Simpy; Kim, Youngkuk; Park, Jinjoo; Lee, Youngseok; Cho, Young Hyun; et al.
Abstract: Effective carrier contact with excellent surface passivation is essential for archiving high efficiency silicon solar cells. In this study, optical, passivation and stoichiometric characteristics of MoOx thin films were analyzed by varying thickness, temperature and ambient annealing. The 10 nm thick MoOx films showed high optical transmittance (89.81%) in the visible near infra-red (NIR) wavelength (380–1100) nm region and wide optical bandgap of 3.25 eV. An improved minority carrier lifetime of 2.24 ms was recorded for O2 ambient at 130 °C due to less additional defects in the MoOx films. X-rays photoelectron spectroscopic analysis confirmed that O2 ambient annealing greatly influenced the MoOx stoichiometric and reduce the formation defective state densities at the Fermi energy initiating from the tail of an oxygen vacancy and inducted the defect band within the energy bandgap. Carrier selective contact (CSC) solar cells were fabricated by using 10 nm thick MoOx film as hole extraction layer exhibited the high performance as; open circuit voltage (Voc ) = 708 mV, current density (Jsc ) = 37.80 mA/cm 2, fill factor (FF) = 74.95% and efficiency (η) = 20.06%. These results implies that the MoOx is an important material to use in future CSC solar cell applications with the concept of new advantages such as dopant free, non-toxic and low temperature fabrication process.